Porównanie w poezji Tadeusza Różewicza (lata 1945–1950) - Kudra, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
The author subjected a hundred and fifteen comparisons included in Tadeusz Różewicz’s poems from the years 1945–1950 to an analysis. He was exploring the components of the comparison: tertium comparationis, comparandum, comparans; the grammatical functor and formal variants of the comparisons, thematical ranges. The author was also analyzing the question of the delimitation of that troop. Chosen conclusions: the most numerous are the developed comparisons with a frequent metaphor in their boundary – they are multifunction comparisons, ample semantically. The author also introduced ideas of a closer and farther tertium comparationis.